A comparative study of pregnancy outcomes among women with and without threatened miscarriage in the first trimester in Abakaliki Southeast Nigeria - Nwafor, Johnbosco Ifunanya; Onuchukwu, Victor Jude Uchenna; Obi, Vitus Okwuchukwu; Ugoji, Darlinghton-Peter Chibuzor; Onwe, Blessing Idzuinya; Ibo, Chukwunenye Chukwu; Obi, Chuka Nobert (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background:Threatened miscarriage is the commonest complication of pregnancy and has been a Background: Threatened miscarriage is the commonest complication of pregnancy and has been associated with adverse pregnancy outcomes. Therefore, the aim of this study is to determine the association between threatened miscarriage and adverse maternal and perinatal outcomes. Methods: This was a retrospective case-control study undertaken at the Alex Ekwueme Federal University Teaching Hospital, Abakaliki. The study involved 228 women presenting with threatened miscarriage in the first trimester and 228 asymptomatic matched controls. The statistical analysis was done using Epi info version 7.1.5, March 2015 (CDC, Atlanta, Georgia, USA). Results: Women with threatened miscarriage were more likely to have preterm delivery (OR = 7.1, 95% CI = 3.51-14.32, P <0.0001), placenta praevia (OR = 2.4, 95% CI = 1.13 - 5.26, P = 0.03), placental abruption (OR = 3.6, 95% CI = 1.40 - 9.03, P = 0.01) and retained placenta (OR = 2.9, 95% CI = 1.18 - 6.97, P = 0.02). Similarly, women with first trimester threatened miscarriage were more likely to develop postpartum haemorrhage (OR = 2.4, 95% CI = 1.17 - 5.06, P = 0.02). There was no significant differences in the stillbirth rate, Apgar scores at 5 minutes less than 7, admission into neonatal intensive care unit and early neonatal death. Threatened miscarriage was associated with intrauterine growth restriction (OR = 3.5, 95% CI = 1.77 - 6.88, P <0.0001) and low birth weight <2.kg (OR = 3.2, 95% CI = 1.33 - 7.69, P = 0.01). Conclusions: Women with threatened miscarriage in the first trimester are at increased risk of adverse pregnancy outcomes and the risk factors should be taken into consideration when deciding upon antenatal surveillance and management of their pregnancies.